Patients as teachers: Evaluating the experiences of volunteer inpatients during medical student clinical skills training - Elfassy, Michael David; Duncan, Laura; Green, Alison; Sun, Hening; Guimond, Tim; Tzanetos, Katina; Nyhof-Young, Joyce (Canadian Medical Education Journal, 2020)
Purpose: Early patient exposure in medical education is an important element of clinical skill development. This study explores the experiences of volunteer inpatients (VIPs) participating in clinical skills training with junior medical students (JMS) solely for educational purposes. Methods: Following first-year medical students practicing history taking and clinical examinations on VIPs at Toronto General Hospital (TGH) and Toronto Western Hospital (TWH), patients completed a questionnaire and a short audio-recorded interview. This study used a mixed methodological approach. A 5-point Likert-scaled survey queried satisfaction regarding the recruitment process, student and faculty interactions and patient demographics (e.g. age and educational background). A 10-minute follow-up interview investigated patient perspectives. Survey responses were correlated to patient demographics and descriptive thematic analysis summarized trends in patient perspectives. Results: Of 93 consenting VIPs, 66% were male and 58% participated at TGH. The mean overall experience was positive (4.76 and 4.93 at TGH and TWH, respectively). Three themes emerging through thematic analysis were Not “Just” a Medical Student, Patient as Teacher, and Promoting Best Practices. VIPs had positive experiences when students communicated effectively through active listening and engaging patients, and when the VIP role was adequately explained during recruitment. Conclusion: Study results provide clarity about VIP experiences with JMS and lay a foundation for improved patient satisfaction and best practices within clinical skills curricula in the health professions.